Pancasila Ideology: The Importance of the Role of Students and the Government in Upholding the Ideology of Pancasila - Andri Fadillah; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2023)
Background. Pancasila is the foundation of our beloved country, the Republic of Indonesia, where Pancasila serves as a guideline, guide and as the foundation of a country. Purpose. The purpose of the Pancasila Ideology is a collection of values, norms, and ideals that are a reference in achieving the goals of the Indonesian nation. Pancasila is an open ideology that is able to harmonize with the dynamics of Indonesian society. Method. The research used is qualitative and quantitative data by conducting an online survey to the closest people to fill out an opinion forum on the importance of the role of students and the government in upholding the ideology of Pancasila. Results. Like any country, the understanding and application of the State Ideology must be instilled to its people as early as possible. The introduction can be done through the introduction of history, education and the environment. Meanwhile, in this global era, outside cultures such as songs, spectacles and information enter swiftly without adequate control Conclusion. The conclusion is that the role of students as agents of change has great potential in stemming the neglect of Pancasila as a state ideology because students are the people who will take control of the country in the future.